Six New Methyl Apiofuranosides from the Bark of Phellodendron chinense Schneid and Their Inhibitory Effects on Nitric Oxide Production - Wang, Peng-Fei (Molecules, 2019)
A chemical investigation on 70% EtOH extract from the bark of Phellodendron chinense Schneid (Rutaceae) led to six new methyl apiofuranosides (1–6), and ten known compounds (7–16). All these compounds were characterized by the basic analysis of the spectroscopic data including extensive 1D-, 2D-NMR (HSQC, HMBC), and high-resolution mass spectrometry, and the absolute configurations were determined by both empirical approaches and NOESY. Inhibitory effects of compounds 1–9 and 11–16 on nitric oxide production were investigated in lipopolysaccharide (LPS)-mediated RAW 264.7 cells, as a result, most of these isolates inhibited nitric oxide (NO) release, and among them 9, 11, and 12 displayed the strongest inhibition on NO release at the concentration of 12.5 μM.